Historical Responsibility and Liberal Society - Janna Thompson (Intergenerational Justice Review)
Why should leaders of polities, as representatives of citizens, be required to apologise and make reparations for deeds committed in the historical past? Assumptions commonly made by liberals about the scope of responsibility and the duties of citizens make this question difficult to answer. This paper considers some unsuccessful attempts within a liberal framework to defend obligations of reparation for historical injustices and puts forward an account based on the lifetime-transcending interests of citizens.